2018
DOI: 10.1253/circj.cj-17-0379
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Pulmonary Vascular Reverse Remodeling After Pulmonary Artery Banding Performed in Early Infancy in Patients With Congenital Heart Defects

Abstract: for PAB from the view point of reversibility of pulmonary vascular lesions has not been fully described. The aim of this study was to evaluate pulmonary vascular reverse remodeling after PAB using serial lung biopsy specimens and to draw conclusions on the optimal timing for PAB in terms of pulmonary vascular reverse remodeling. Methods SubjectsNumerous lung biopsy and autopsy specimens have been collected from multiple centers in Japan for diagnosing pulmonary vascular disease (PVD). Out of a total of 1,293 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…After PAB, the %MS, %MT, and APSC all significantly decreased, suggesting that although grade III was the critical state of the lesion, it was still reversible. These results are supported by a study by Masaki et al [10], who showed that pulmonary arterial remodeling could be reversed after PAB. They also showed that this reversal was more important for children < 6 months of age [10], as supported by previous studies [28,29].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…After PAB, the %MS, %MT, and APSC all significantly decreased, suggesting that although grade III was the critical state of the lesion, it was still reversible. These results are supported by a study by Masaki et al [10], who showed that pulmonary arterial remodeling could be reversed after PAB. They also showed that this reversal was more important for children < 6 months of age [10], as supported by previous studies [28,29].…”
Section: Discussionsupporting
confidence: 80%
“…These results are supported by a study by Masaki et al [10], who showed that pulmonary arterial remodeling could be reversed after PAB. They also showed that this reversal was more important for children < 6 months of age [10], as supported by previous studies [28,29]. Nevertheless, the present study suggests that significant vascular remodeling takes place even when PAB is performed after 2 years of age.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations